166k views
3 votes
What is the quotient (125 – 8x3) ÷ (25 + 10x + 4x2)? –2x + 5 2x – 5 –2x – 5 2x + 5

User Uthomas
by
5.6k points

2 Answers

1 vote

Answer:

The quotient is (5-2x)

Explanation:

Given the expression
\frac{125-8{x}^(3)}{25+10x+4{x}^(2)}

We have to simplify the above expression to find the quotient.


\frac{125-8{x}^(3)}{25+10x+4{x}^(2)}


\frac{5^3-{2x}^(3)}{25+10x+4{x}^(2)}

By the identity


{a}^(3)-{b}^(3)=(a-b)({a}^(2)+ab+{b}^(2))

Here, a=5 and b=2x

gives
{5}^(3)-{2x}^(3)=5^2+5(2x)+(2x)^2=25+10x+4x^2

∴ expression becomes


\frac{125-8{x}^(3)}{25+10x+4{x}^(2)}=\frac{(5-2x)(25+10x+4x^2)}{25+10x+4{x}^(2)}=(5-2x)

Hence, the quotient becomes (5-2x)

User Doddy
by
6.3k points
4 votes
ANSWER


\frac{125 - 8 {x}^(3) }{ 25 + 10x + 4 {x}^(2) } = - 2x+5

EXPLANATION

We have been given the quotient,


\frac{125 - 8 {x}^(3) }{ 25 + 10x + 4 {x}^(2) }
to simplify.

We need to rewrite the numerator as difference of two cubes.


\frac{125 - 8 {x}^(3) }{ 25 + 10x + 4 {x}^(2) } = \frac{ {5}^(3) - ( {2x})^(3) }{ 25 + 10x + 4 {x}^(2) }

We need to make use of the difference of cubes formula,


{a}^(3) - {b}^(3) = (a - b)( {a}^(2) + ab + {b}^(2) )

We now let,

a = 5 \: and \: b = 2x

Then the numerator becomes,


\frac{125 - 8 {x}^(3) }{ 25 + 10x + 4 {x}^(2) } = \frac{ (5 - 2x)(25 + 5 (2x) + {(2x)}^(2)) }{ 25 + 10x + 4 {x}^(2) }

This simplifies to,


\frac{125 - 8 {x}^(3) }{ 25 + 10x + 4 {x}^(2) } = \frac{ (5 - 2x)(25 + 10x + 4 {x}^(2)) }{ 25 + 10x + 4 {x}^(2) }

We cancel out common factors to obtain,


\frac{125 - 8 {x}^(3) }{ 25 + 10x + 4 {x}^(2) } = ( (5 - 2x))/( 1)


\frac{125 - 8 {x}^(3) }{ 25 + 10x + 4 {x}^(2) } = 5 - 2x
User RoryB
by
6.4k points